2010
DOI: 10.1007/s10508-010-9621-4
|View full text |Cite|
|
Sign up to set email alerts
|

The Relationship Among Sexual Attitudes, Sexual Fantasy, and Religiosity

Abstract: Recent research on the impact of religiosity on sexuality has highlighted the role of the individual, and suggests that the effects of religious group and sexual attitudes and fantasy may be mediated through individual differences in spirituality. The present study investigated the role of religion in an ethnically diverse young adult sample (N = 1413, 69% women) using religious group as well as several religiosity domains: spirituality, intrinsic religiosity, paranormal beliefs, and fundamentalism. Difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(52 citation statements)
references
References 47 publications
5
45
1
1
Order By: Relevance
“…These results are in accordance with literature (Reiss, 1967, Ahrold, Farmer, Trapnell, & Meston, 2011, Brelsford, Luquis, & Murray-Swank, 2011, where religiosity was found to be associated with more conservative sexual attitudes.…”
Section: Eissn: 2357-1330 Selection and Peer-review Under Responsibilsupporting
confidence: 93%
“…These results are in accordance with literature (Reiss, 1967, Ahrold, Farmer, Trapnell, & Meston, 2011, Brelsford, Luquis, & Murray-Swank, 2011, where religiosity was found to be associated with more conservative sexual attitudes.…”
Section: Eissn: 2357-1330 Selection and Peer-review Under Responsibilsupporting
confidence: 93%
“…Importantly, the suggested mechanism causing this relationship is that moral views are transferred from a social network to the focal individual, and these moral views then shape the individual's behavior (see also Adamczyk & Palmer, 2008). Similar proposals have been made to explain variation in sexual attitudes: In the U.S., increased church attendance and being a member of a more conservative denomination are related to morally conservative sexual views, arguably because religious social networks preach conservative sexual views (Adamczyk & Pitt, 2009;Ahrold, Farmer, Trapnell, & Meston, 2011;Cochran & Beeghley, 1991;Petersen & Donnenwerth, 1997). Thus, the background assumption of these studies is that religious commitment, for example if it embeds one in a religious social network, shapes moral views towards drugs and sex, which in their turn shape behavior.…”
Section: Ideological Theoriesmentioning
confidence: 90%
“…Zaleski and Schiaffino (2000) found adolescents with high religious identification who were sexually active reported less frequent condom use. Ahrold et al (2011) found similar negative attitudes toward condom use in those who were fundamentally religious. Lefkowitz et al (2004) found decreased sexual activity among emerging adults with higher levels of religiosity.…”
Section: Sex and Level Of Religious Commitmentmentioning
confidence: 75%
“…Rowatt and Schmitt (2003) found that individuals with intrinsic religious motivation, those who internalize religious teachings and values, were more sexually restricted and desired less sexual variety than those with extrinsic religious motivation, those who engage in religious activities in order to gain benefits such as community but adhere minimally to religious teachings. Intrinsically religious and fundamentally religious women also report lower frequency of sexual fantasy (Ahrold et al 2011). In a study of sexual fantasy experiences among conservative Christians, participants reported their behavior as morally unacceptable and engaging in sexual fantasizing provoked guilt and anxiety (Gil 1990).…”
Section: Sex and Level Of Religious Commitmentmentioning
confidence: 99%